2009
DOI: 10.1111/j.2040-0209.2009.00334_2.x
|View full text |Cite
|
Sign up to set email alerts
|

Who Are ‘Informal Health Providers’ and What Do They Do? Perspectives from Medical Anthropology

Abstract: About IDSThe Institute of Development Studies is one of the world's leading organisations for research, teaching and communications on international development. Founded in 1966, the Institute enjoys an international reputation based on the quality of its work and the rigour with which it applies academic skills to real world challenges. Its purpose is to understand and explain the world, and to try to change it -to influence as well as to inform.IDS hosts five dynamic research programmes, five popular postgra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 46 publications
0
10
0
1
Order By: Relevance
“…) found that informal providers make up a significant portion of the healthcare sector globally. Manifold definitional problems beset comparison in this field, not least concerning the kinds of practitioner included under the rubric of ‘informal provider’ (see Cross and MacGregor ). But studies from Bangladesh (Ahmed et al .…”
Section: Discussionmentioning
confidence: 68%
See 4 more Smart Citations
“…) found that informal providers make up a significant portion of the healthcare sector globally. Manifold definitional problems beset comparison in this field, not least concerning the kinds of practitioner included under the rubric of ‘informal provider’ (see Cross and MacGregor ). But studies from Bangladesh (Ahmed et al .…”
Section: Discussionmentioning
confidence: 68%
“…Symbols of biomedical practice – like injections, the use of the stethoscope, blood pressure apparatus and glucometer, or advertising a ‘clinic’ – also by association convey to clients an RMP's credentials as an allopathic practitioner (cf. Cross and MacGregor , Pinto ). In one case, an elderly Muslim Unani practitioner saw his four sons all become RMPs, situating themselves as his inheritors, but unlike their father located pragmatically and rhetorically within biomedicine.…”
Section: Biomedicine Domesticated: the Popularity Of Rmpsmentioning
confidence: 99%
See 3 more Smart Citations